MARRIAGE WITHOUT THE CONSENT OF ONE OF THE PARENTS FROM THE PERSPECTIVE OF ISLAMIC FAMILY LAW - Ridwan, Muhammad; Harahap, Purnama Hidayat (Universitas Islam Negeri Sumatera Utara Medan, 2023)
Marriage without the consent of one parent is a complex phenomenon in Islamic family law, raising a variety of legal, social, and cultural questions. In this context, the role of the guardian as a determinant of marriage consent is crucial, because the guardian is responsible not only to protect the interests of the bride-to-be, but also to ensure the validity of the marriage law. However, in practice, there are variations in interpretation among Islamic schools regarding the necessity of guardian consent, creating challenges in the consistency of universal application of Islamic family law. The issue also highlights the conflict between the individual's right to choose his or her own life partner and the social and traditional expectations that require parental consent. This study aims to investigate the legal, social, and psychological implications of marriage without the consent of one parent in the context of Islamic family law, as well as to explore the role of religious courts in resolving disputes that arise.